Impediments to Disability Accommodation - Williams-Whitt, Kelly (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2007)
The results of a qualitative field investigation exploring how tripartite relationships affect disability accommodations are reported. Arbitration cases, in-depth interviews and other documentation are analyzed using grounded theory techniques. Four key categories emerge as contributors to difficult accommodations. The first category suggests that managerial reluctance and bias may stem from added workload or from questions about disability credibility. It further demonstrates how trust issues spill over to affect future accommodations. The second category, employee involvement, indicates that excluding the disabled employee from accommodation planning occurs frequently and has a negative affect on communication patterns, again damaging trust. The third category, ineffective investigation, highlights the difficulty managers have balancing confidentiality requirements: over-investigating illness legitimacy and under-investigating accommodation options. The final category, union-management climate, looks at union roles in accommodation and suggests that while unions often play a unique and positive role, substantial union-management animosity taints return-to-work efforts.